The citizen participation in the Management of Urban Heritage of the city of Cuenca (Ecuador) - Rey Pérez, Julia; Tenze, Alicia (Estoa. Journal of the Faculty of Architecture and Urbanism, 2018)
Heritage cities are threatened by pressures such as climate change, market forces, urbanization, mass tourism, immigration..., among many other factors that affect their conservation. Likewise, the urban management of these heritage cities is mainly carried out in the public administration and rarely academic support is taken into account, but there are few examples that incorporate the perception and opinion of citizenship as another input to develop the Strategic Plans for the management of urban heritage. However, the case of Cuenca in Ecuador is an example of how, through the implementation of the Recommendation on the Historic Urban Landscape, and in particular, with the development of Step 2 related to urban governance and the taking of decisions from the bottom up, it is possible to incorporate from the beginning the citizenship in the decision making and in the process of drawing up these Strategic Plans. Only from these forms of participative planning and management it is ensured that the urban development of the city of Cuenca can be an example of sustainability, where heritage and citizenship play a leading role.